2024
DOI: 10.3389/fpubh.2024.1264292
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in adapting a stroke unit in a middle-income country: warning about costs and underfunding to achieve the Brazilian Ministry of Health’s benchmark

Natalia Cristina Ferreira,
Gustavo José Luvizutto,
Silméia Garcia Zanati Bazan
et al.

Abstract: BackgroundSince the implementation of the stroke care line in Brazil, the relationship (adequacy) of costs spent during hospitalization with the Brazilian Ministry of Health indicators for a stroke unit have not yet been analyzed.AimsThis study aimed to assess the adequacy of a comprehensive stroke center for key performance indicators and analyze the costs involved in hospitalization. We verified the association between stroke severity at admission and care costs during hospitalization.MethodsA retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…This timeframe is consistent with data from European registries, which reported a mean time of 70 min [30]. Despite the increase in thrombolysis frequency post-SU implementation (6.1% to 10.8%), it remained relatively low, underscoring the ongoing need to strengthen the stroke survival chain [29]. However, this is similar to the reality in northern and southern European countries, where only 7.3% of all AIS patients receive thrombolysis, reflecting an unequal geographical SU distribution [31].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This timeframe is consistent with data from European registries, which reported a mean time of 70 min [30]. Despite the increase in thrombolysis frequency post-SU implementation (6.1% to 10.8%), it remained relatively low, underscoring the ongoing need to strengthen the stroke survival chain [29]. However, this is similar to the reality in northern and southern European countries, where only 7.3% of all AIS patients receive thrombolysis, reflecting an unequal geographical SU distribution [31].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the number of thrombolysis patients within <60 min post-SU implementation increased from 7 to 25. Although modest, these findings parallel those of a study conducted in Botucatu (SP), which also identified a small number of patients undergoing thrombolytic treatments with door-to-needle times <60 min [29]. This timeframe is consistent with data from European registries, which reported a mean time of 70 min [30].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation